ESTIMATION OF MAXIMUM WATER FLOW IN CASE OF INSUFFICIENT DATA OF HYDROMETRIC OBSERVATIONS ON THE EXAMPLE OF THE SIRET RIVER BASIN - Melnik, Anton; Berezka, Ihor; Yavkin, Vyacheslav (Науковий вісник Чернівецького університету: збірник наукових праць. Чернівці: ЧНУ, 2019. –Вип. 814: Географія –С. 4-8., 2019)
Catastrophic flood hydrograph components are formed depending on spat¬ial variation and seasoning of meteorological elements. However, from year to year, the role of anthropogenic factors becomes more and more substantial, and the latter significantly effect on the duration of flood passage. The time series of max¬i-m¬al flow rates within natural-economic basin system of the Siret River were con¬sid-ered in the present work, which, with the use of the rivers-analogues, allowed for specification of said rates’ values at 1% provision probability. In comparison to previous publications, too generalized data were highlighted in more detail, thus adding to differentiation of maximal flow rates distribution. The maximal flow rates were put to prolonged series of observation, and the obtained values were compared to those in previous publications by other authors who made use of significantly short¬er series within the territory of the study. The results allowed for the assertion that the maximal flow rates essentially decreased in all observation sites at 1% excess probability. The biggest value of maximal flow rate at 1% excess probability was characteristic for the Siret River-Town of Storozhynets, while the lowest – for the Mykhydra River-Village of Lypovany.
ESTIMATION OF MAXIMUM WATER FLOW IN CASE OF INSUFFICIENT DATA OF HYDROMETRIC OBSERVATIONS ON THE EXAMPLE OF THE SIRET RIVER BASIN
http://geochnu.top/index.php/climat_geology/article/view/24/20
Keywords: maximal flow; prolonged series; drain module